Rapid detection of vaginitis in reproductive age group-by immunochromatography method (Bangladesh Journal of Medical Microbiology, 2016)
Vaginitis is the most frequent gynaecologic diagnosis encountered by physician providing primary care to the women. It is defined as inflammation and/or irritation of the vagina, a troublesome condition that affects millions of women in all parts of the world. A total of 50 women of reproductive age within 15-45 years, both pregnant and non-pregnant with abnormal vaginal discharge were enrolled in the study. Vaginal fluid was collected from the patients attending outpatient department of Dhaka Medical College & Hospital. A rapid vaginal immunochromatography kit were used to test the samples for Chlamydia, Trichomonas, Candida and Gardnerellavaginalis along with pH, nitrites, protein and leucocytes. Bacterial vaginitis was diagnosed in 16%, 20% and 18% of the cases using microscopy, culture and rapid vaginal test kit respectively, whereas, was detected in 16%, 8%, 16% by microscopy, culture and rapid vaginal kit respectively in case of bacterial vaginosis. Chlamydia(6.66%) and Trichomonas (6.66%) was detected in the vaginal kit and Candida was detected in 3.33% cases using all three methods. Rapid vaginal kit is a simple, rapid test (result within 10 minutes) and can be used as a point of care test or for screening large number of samples.Bangladesh J Med Microbiol 2016; 10 (2): 18-21